A comparison of cholecystitis grading scales. Issue 3 (March 2019) - Madni, Tarik D.; Nakonezny, Paul A.; Imran, Jonathan B.; Taveras, Luis; Cunningham, Holly B.; Vela, Ryan; Clark, Audra T.; Minshall, Christian T.; Eastman, Alexander L.; Luk, Stephen; Phelan, Herb A.; Cripps, Michael W.
Abstract : BACKGROUND: Previously, our group developed the Parkland grading scale for cholecystitis (PGS) to stratify gallbladder (GB) disease severity that can be determined immediately when performing laparoscopic cholecystectomy (LC). In prior studies, PGS demonstrated excellent interrater reliability and was internally validated as an accurate measure of LC outcomes. Here, we compare PGS against a more complex cholecystitis severity score developed by the national trauma society, American Association for the Surgery of Trauma (AAST), which requires clinical, operative, imaging, and pathologic inputs, as a predictor of LC outcomes. METHODS: Eleven acute care surgeons prospectively graded 179 GBs using PGS and filled out a postoperative questionnaire regarding the difficulty of the surgery. Three independent raters retrospectively graded these GBs using PGS from images stored in the electronic medical record. Three additional surgeons then assigned separate AAST scores to each GB. The intraclass correlation coefficient statistic assessed rater reliability for both PGS and AAST. The PGS score and the median AAST score became predictors in separate linear, logistic, and negative binomial regression models to estimate perioperative outcomes. RESULTS: The average intraclass correlation coefficient of PGS and AAST was 0.8647 and 0.8341, respectively. Parkland grading scale for cholecystitis was found to be a superior predictor of increasing operative difficulty ( R 2, 0.566 vs. 0.202), case length ( R 2, 0.217 vs. 0.037), open conversion rates (area under the curve, 0.904 vs. 0.757), and complication rates (area under the curve, 0.7039 vs. 0.6474) defined as retained stone, small-bowel obstruction, wound infection, or postoperative biliary leak. Parkland grading scale for cholecystitis performed similar to AAST in predicting partial cholecystectomy, readmission, bile leak rates, and length of stay. CONCLUSION: Both PGS and AAST are accurate predictors of LC outcomes. Parkland grading scale for cholecystitis was found to be a superior predictor of subjective operative difficulty, case length, open conversion rates, and complication rates. Parkland grading scale for cholecystitis has the advantage of being a simpler, operative-based scale which can be scored at a single point in time. LEVEL OF EVIDENCE: Single institution, retrospective review, level IV.